Arabic text - Abuzaraida, Mustafa; Zeki, Akram M. (IIUM Press, 2015)
Text recognition is one of the most interesting subjects in language recognition. It was investigated and studied by several researchers who worked on characters in general that might by handwritten or typewritten. These researchers tried to cover diverse areas in this subject by discussing, analyzing, comparing and implementing algorithms for each phase of the recognition are fewer who compared to those conducted in other language e.g. Latin and Chinese. This could be due to the unsolved challenges in Arabic language, though it is now gaining interest from many researchers (Tagougui, Kherallah & Alimi, 2012)